SOLUTION: I'm really confused trying to solve this equation. I keep getting different answers. I think the bx is confusing me. 3bx + 9 = 4(3x-b)+2 solve for x

Algebra ->  Algebra  -> Equations -> SOLUTION: I'm really confused trying to solve this equation. I keep getting different answers. I think the bx is confusing me. 3bx + 9 = 4(3x-b)+2 solve for x      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Equations Solvers Lessons Answers archive Quiz In Depth

 Question 1644: I'm really confused trying to solve this equation. I keep getting different answers. I think the bx is confusing me. 3bx + 9 = 4(3x-b)+2 solve for xFound 2 solutions by usyim88hk, Scorinitron:Answer by usyim88hk(157)   (Show Source): You can put this solution on YOUR website!3bx+9 = 4(3x-b)+2 First, multiply 4 with (3x-b) 3bx+9 = 12x-4b+2 Now munis 9 from both sides and minus 12x from both sides 3bx-12x = -4b-7 Factor 3bx-12x 3x(b-4) = -4b-7 Divide both sides by (b-4) 3x = (-4b-7)/(b-4) Now divide both sides by 3 x = (-4b-7)/(3b-12) Answer by Scorinitron(19)   (Show Source): You can put this solution on YOUR website!I'm going to be real. This was hard...and confusing but here's what I did. The Problem 3bx+9=4(3x-b)+2 ____________________ The Steps: ______________________ Multiply 4 by each term inside the parentheses. 3bx+9=12x-4b+2 Since 12x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 12x from both sides. 3bx+9-12x=-4b+2 Factor out the GCF of 3x from each term in the polynomial. 3x(b)+3x(-4)=-4b-7 Factor out the GCF of 3x from 3bx-12x. 3x(b-4)=-4b-7 Divide each term in the equation by (b-4). (3x(b-4))/(b-4)=-(4b)/(b-4)-(7)/(b-4) Simplify the left-hand side of the equation by canceling the common factors. 3x=-(4b)/(b-4)-(7)/(b-4) Simplify the right-hand side of the equation by simplifying each term. 3x=(-4b-7)/(b-4) Divide each term in the equation by 3. (3x)/(3)=(-4b-7)/(b-4)/(3) Simplify the left-hand side of the equation by canceling the common factors. x=(-4b-7)/(b-4)/(3) Simplify the right-hand side of the equation by simplifying each term. x=(-4b-7)/(3(b-4))